Primary healthcare utilization by the elderly: a secondary analysis of the 5th Indonesian Family Life Survey. Issue 2 (7th April 2020) - Chen, Ching-Min; Baithesda, Baithesda
Abstract : Purpose: The purpose of this study is to examine different types of primary healthcare utilization and its influencing factors among the elderly in Indonesia. Design/methodology/approach: Data were obtained from the 5th Indonesian Family Life Survey, a longitudinal database of demography and health information using multistage stratified sampling of households. Older adults aged at least 60 years were sampled; proxy respondents and incomplete data were excluded from the study. Findings: Most of the elderly preferred to visit nurse/midwives practitioner (NP), followed by the community health centers (CHC). Those who lived outside of the Java region were more likely to visit NP; moreover, those without formal education and lived in the rural area were more likely to use CHC. Education level, region and chronic conditions were significant predicting factors for almost all types of primary healthcare use. Social implications: Indonesia is moving towards an aged society in the coming decades. However, there are significant barriers to access almost all types of primary health care by the elderly in Indonesia. This shows the possibility of health care inequality for the elderly population. This study provides evidence of the various types of primary healthcare use by the elderly and its influencing factors. It hopes policymakers can use the data to develop an effective strategy to enhance the quality of primary healthcare services provides to the elderly population. Originality/value: Indonesian nurses fulfill vital functions in the health system and are often the only human resource for health not only in remote and poor rural areas but also in urban areas. Nurses, as a part of primary care providers, require an adequately trained to contribute to the better primary care system.